EDUCATIONAL STANDARDS IN EUROPEAN COUNTRIES - Abdulhamidova Hanifa (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
ANNOTATION: Each country in Europe has a different education system and curriculum. And these have evolved over the centuries, based mainly on changing economic, cultural, social, and political conditions. So what does the education system look like in Poland today? In the European Union, there’s no uniform educational policy. No higher institution intervenes or imposes specific requirements regarding education in these countries.